تأثير إضافة معامل الزمن على أداء الشبكة العصبية الاصطناعية في تقدير التّبخر اليومي في المنطقة الجبلية من الساحل السوري - عمار غطفان; حيدر بادية (Latakia University Journal -Engineering Sciences Series, 2017)
يلعب التبخر دوراُ بارزاُ في الدورة الهيدرولوجية والتوازن المائي، وتعد عملية حساب كمية المياه المتبخرة من أكثر المسائل التي تهتم بها الدراسات الهيدرولوجية الحديثة، حيث تم مؤخراً تطبيق الشبكات العصبية الاصطناعية كأداة قوية لزيادة القدرة على التنبؤ بالعلاقات الخطية وغير الخطية في المشاكل الهندسية المعقدة. تهدف هذه الدراسة إلى بناء أنموذج رياضي لتقدير التبخر من المنطقة الجبلية من الساحل السوري، باستخدام الشبكة العصبية الصنعيَّة وذلك اعتماداً على أربعة بارمترات جوية، وهي درجة الحرارة، الرطوبة النسبية، سرعة الرياح والسطوع الشمسي، ومن ثم دراسة تأثير إضافة معامل الزمن على تقدير التبخر. بني الأنموذج الرياضي باستخدامNeural Fitting Tool إحدى أدوات الماتلاب، وقد اعتمد على البيانات اليومية للبارامترات المذكورة في منطقة الدراسة بالإضافة إلى معامل الزمن، كما استُخدِمت بيانات التبخر اليومي المقيسة بوساطة حوض التبخر الأميركي صنف A كمخرجات مأمولة لغرض التحقق من صحة أداء الشبكة. وتظهر النتائج تفوق الشبكة المضاف لها معامل الزمن حيث بلغ معامل الارتباط فيها لمجموعة التحقق 0.8919 ومتوسط مربع الخطأ 0.02166 بينما كانت قيمة معامل الارتباط للشبكة المستخدمة للتنبؤ بقيمة التبخر اعتماداً على المعطيات المناخية بدون إدخال معامل الزمن 0.8324 ومتوسط مربع الخطأ 0.0327. Evaporation plays a prominent role in the hydrological cycle and water balance, where the computation of evaporated water amount is considered one of the more practical issues of interest to the modern hydrological studies. The artificial neural networks have been applied as a powerful tool to increase the predictability of linear and non-linear relationships in complex engineering problems. This study is aiming at building a mathematical model to estimate evaporation from Mountainous region in Syrian Coast, using an artificial neural network, based on four metrological parameters (i.e. temperature, relative humidity, wind speed and sun hours), then studying the effect of adding time variable on evaporation estimation. The mathematical model was built by the (NN-tool box), which is one of the MATLAB tools, using the daily value of the above mentioned parameters in addition to time, as the network inputs and the evaporation measured from the American pan class A as the network output . The results show that ANN4+T model which have 5 inputs (temperature, relative humidity, wind speed, sun hours, time) is the best in estimation evaporation with correlation factor of 0.8919 and Mean square error of 0.02166 for the validation set where the correlation factor in ANN4 (without time) was 0.8324 and MSE of 0.0327for the validation set.